Improved cotton yield: Can we achieve this goal by regulating the coordination of source and sink? - Qin, Aizhi; Aluko, Oluwaseun Olayemi; Liu, Zhixin; Yang, Jincheng; Hu, Mengke; Guan, Liping; Sun, Xuwu (Frontiers in Plant Science, 2023)
Cotton is one of the major cash crops globally. It is characterized by determinate growth and multiple fruiting, which makes the source-sink contradiction more obvious. Coordination between source and sink is crucial for normal growth, yield, and quality of cotton. Numerous studies reported how the assimilate transport and distribution under varying environmental cues affected crop yields. However, less is known about the functional mechanism underlying the assimilate transport between source and sink, and how their distribution impacts cotton growth. Here, we discussed not only the assimilate transport and distribution mechanisms but also those involved in the source-sink relationship, and their relation to cotton yield. Therefore, this review would enrich our knowledge of the regulatory mechanism, which can then be targeted to modulate the source-sink relationship for improved cotton yield.